Pengaruh Penerapan Aplikasi Ulead Video Studio Terhadap Motivasi Belajar Siswa Kelas IV MI Munawariyah Palembang - Wina Calista (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to determine the effect of the application of studio video ulead application on the learning motivation of fourth grade students in the subjects of Islamic Culture History in Palembang MI Munawariyah. From these findings it can be described the results of the pretest of students who get the highest score are 7 students (24%), who get a moderate score of 10 students (34%) and who get a low score of 12 students (41%). And the posttest of students who got the highest score were 14 students (48%), who were classified as 10 students (34%) and those who received the lowest score were 5 students (17%). Third, the significance of the influence of student motivation before and after by comparing the magnitude of